Extracranial Carotid Artery Aneurysms: 20-Year Experience of Surgical Management - Ihor I. Kobza; Yuliya S. Mota; Taras I. Kobza (Ukrainian Journal of Cardiovascular Surgery, 2022)
Extracranial carotid artery aneurysm (ECAA) is a rare vascularpathology with reported incidence of 0.2-5.0% of all carotid artery surgical interventions. Most of ECAAs remain clinically asymptomatic, however, they can manifest in neurological symptoms as transient ischemic attack or stroke. The presence of a pulsating formation, swallowing disorders, signs of compression of cranial nerves may beindicative of the aneurysm growth, which is associated with higher risk of thromboembolic complications and less oftenwith rupture. Surgical treatment is a method of choice in symptomatic patients or in cases of the aneurysm growth and includes resection with arterial reconstruction, ligation of the artery or endovascular intervention.The aim. To improve the results of surgical treatment of ECAAs.Materials and methods. The results of clinical examination, laboratory, instrumental, intraoperative observations were analyzed in 39 patients (35 [89.7%] men and 4 [10.3%] women) with 44 ECAAs, who were admitted to the Vascular Surgery Department of Lviv Regional Clinical Hospital for the period from 2003 to 2022. To conϐirm the diagnosis of ECAA, preoperative instrumental examination included duplex ultrasonography and multispiral computed tomography angiography.Results. Etiological causes of ECAAs included: atherosclerosis (79.5%),ϐibromuscular dysplasia (7.7%), trauma (5.1%), previous operations in the neck region (5.1%) and infection (2.6%). The justiϐication of the choice of surgical tactics depended on the localization of aneurysm, concomitant carotid occlusive disease or pathological deviation of carotid arteries. Early results of surgical treatment were evaluated up to 30 days of the postoperative period. The postoperative complications included: transient ischemic attack in 1 (2.6%), ischemic stroke in 2 (5.1%), cranial nerve damages in 4 (10.3%), thrombosis of arterial reconstruction in 2 (5.1%), hematoma of postoperative wound in 4 (10.3%), infection of postoperative wound in 1 (2.6%) cases. Postoperative mortality was 2.6%.Conclusion. ECAA is a rare clinical disease that requires an active surgical approach to reduce the risk of ischemic stroke. Reconstructive surgery of ECAAs is a highly effective method of treatment that allows to achieve satisfactory results and prevent the development of severe complications.